Muscular kevlar aerogel tapes attractive to thermal insulation fabrics - Jin, YueYang; Tang, YaTing; Cao, WenHao; Yan, YangYang; Sun, Yueyan; Chen, Weiwang (Frontiers in Materials, 2023)
Kevlar aerogel is a kind of easy-casting nano-porous material with the characteristics of low density, high porosity, low thermal conductivity, high specific surface area, etc. It can serve as functional fibers and has a bright future in the field of thermal insulation after being processed into fabrics. To improve the tensile power of aerogel fibers to bear more loads while maintaining their flexibility for further braiding, a series of Kevlar aerogel tapes were fabricated in this study by using flattened needles. It is observed that the resultant aerogel tapes show a spindle-like cross section, and have greatly improved load-bearing capability with muscular tensile strength up to 2.07 MPa. Besides, these tapes also inherit the excellent thermal stability and char-forming ability of Kevlar, starting to decompose at around 500 ℃ and producing carbon residue more than 40 % of their initial weight at 700 ℃. In addition, these Kevlar aerogel tapes also perform well in thermal insulation, better than the previously fabricated aerogel fibers. It can be envisaged that the developed aerogel tapes with muscular tensile strength and their fabric products will be promising for high-temperature thermal insulation applications, such as being used as the insulation layer for thermal protective clothing.